Social representations of pregnant women about pregnancy during prenatal care - Silveira, Maria Adelaide Moura da; Rodrigues, Antonia Regynara Moreira; Dantas, Sibele Lima da Costa; Melo, Laura Pinto Torres de; Fialho, Ana Virgínia de Melo; Rodrigues, Dafne Paiva (Revista de Enfermagem da UFPI, 2024)
Objective: To understand the social representations of pregnant women about pregnancy during the prenatal period. Methods: A qualitative study, guided by the theoretical assumptions of the Social and Methodological Representations of the Convergent Care Research, carried out with 11 pregnant women accompanied by the family health strategy, after approval by the Ethics Committee. For data collection, an in-depth individual interview and the convergence group method were carried out during September to November 2016. The data obtained was subjected to content analysis. Results: Data analysis resulted in two categories: discovery of pregnancy and; pregnancy as a state of change. It was evident that representations of pregnancy are anchored in the realization of the dream and in the religious belief that involves motherhood, as well as in the family constitution and increased sense of responsibility. Final considerations: It is understood from the study that pregnancy, even causing physical, psychological and social changes, is something expected by women and that generates multiple feelings and causes changes.